Bacteremia pathogens in the University Hospital Olomouc - Htoutou Sedlaková, Miroslava; Fišerová, Kateřina; Kolář, Milan (Klinicka mikrobiologie a infekcni lekarstvi, 2020)
OBJECTIVES: To provide an overview of the most common bacterial species isolated from blood cultures in the University Hospital Olomouc in the years 2015-2019 and their antibiotic resistance patterns. MATERIAL AND METHODS: The data were obtained from the laboratory information management system ENVIS LIMS. The results were analyzed retrospectively for the period from January 1, 2015 to December 31, 2019. Among positive blood cultures, the prevalence of bacterial species was assessed and the most frequent species were evaluated for resistance to selected antibiotics. Each sample was processed using standard microbiology methods with the MALDI-TOF MS system. Susceptibility to antibiotics was tested with the microdilution method according to the EUCAST recommendations. RESULTS: Over the study period, a total of 3 400 isolates from blood cultures were included. Coagulase-negative staphylococci were the most prevalent (37 %), followed by Escherichia coli (16 %), Klebsiella pneumoniae (9 %), Staphylococcus aureus (7 %), Streptococcus spp. (5 %), Pseudomonas aeruginosa (4 %), Enterobacter cloacae (2 %), Enterococcus faecalis (2 %) and Enterococcus faecium (2 %). Resistance of E. coli to 3rd generation cephalosporins, piperacillin/tazobactam, gentamicin and fluoroquinolones ranged from 7 % to 33 %. A high percentage of Klebsiella pneumoniae strains (33 %-65 %) was resistant to the above antibiotics. The prevalence of methicillin-resistant Staphylococcus aureus reached 3-7 %. Pseudomonas aeruginosa exhibited resistance to piperacillin/tazobactam, ceftazidime, cefepime, meropenem, ciprofloxacin and gentamicin ranging from 3 % to 46 %. CONCLUSION: Knowing the prevalence of bacterial species from blood cultures and their antimicrobial resistance patterns is important for empirical antibiotic therapy in case of an existing infection. It is advisable to conduct such epidemiological studies as part of antibiotic stewardship.
Keywords: Hospitals; Česká republika; bakteriemie; Microbial Sensitivity Tests; lidé; retrospektivní studie; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Drug Resistance, Bacterial; Bacteria; nemocnice; Czech Republic; Bacteremia; Retrospective Studies; bakteriální léková rezistence; Humans